Loss of H3K27me3 imprinting in the Sfmbt2 miRNA cluster causes enlargement of cloned mouse placentas - Inoue, Kimiko; Ogonuki, Narumi; Kamimura, Satoshi; Inoue, Hiroki; Matoba, Shogo; Hirose, Michiko; Honda, Arata; Miura, Kento; Hada, Masashi; Hasegawa, Ayumi; Watanabe, Naomi; Dodo, Yukiko; et al. (Nature communications, 2020)
Somatic cell nuclear transfer (SCNT) in mammals is an inefficient process that is frequently associated with abnormal phenotypes, especially in placentas. Recent studies demonstrated that mouse SCNT placentas completely lack histone methylation (H3K27me3)-dependent imprinting, but how it affects placental development remains unclear. Here, we provide evidence that the loss of H3K27me3 imprinting is responsible for abnormal placental enlargement and low birth rates following SCNT, through upregulation of imprinted miRNAs. When we restore the normal paternal expression of H3K27me3-dependent imprinted genes ( Sfmbt2 , Gab1 , and Slc38a4 ) in SCNT placentas by maternal knockout, the placentas remain enlarged. Intriguingly, correcting the expression of clustered miRNAs within the Sfmbt2 gene ameliorates the placental phenotype. Importantly, their target genes, which are confirmed to cause SCNT-like placental histology, recover their expression level. The birth rates increase about twofold. Thus, we identify loss of H3K27me3 imprinting as an epigenetic error that compromises embryo development following SCNT. Somatic cell nuclear transfer (SCNT) frequently results in abnormal placenta development in cloned mice. Here the authors show that loss of histone methylation (H3K27me3) imprinting in clustered Sfmbt2 miRNAs contributes to SCNT placenta defect.